The Effect Of Product Quality, Price, And Service Quality On Customer Loyalty at PT. Mitra Niaga Sentratama - Alexander Patrick Sinamo; Dadan Abdul Aziz Mubarok (Journal of Business and Management Inaba, 2025)
The objective of this study is to ascertain how consumer loyalty is at the Mitra Wholesale Store on Kamasan Banjaran Main St. is impacted by service quality, product quality, and price. Customers of Mitra Store made up the study's population, and 80 respondents were included in the sample utilizing non-probability sampling and accidental procedures. Data was gathered via a questionnaire, and the analytic method was multiple linear regression analysis using SPSS statistical software. The t-test was employed in conjunction with the F-test for hypothesis testing. The study's findings indicate that customers who purchase goods from the Mitra Store on at least a twice-weekly basis exhibit a degree of susceptibility to the prices, product quality, and service quality of the store. At Mitra Store, however, judgements to buy products are positively and significantly impacted by the simultaneous test